Burden of idiopathic inflammatory rheumatic diseases in occupational healthcare: increased absenteeism and healthcare resource utilization - Ukkola-Vuoti, Liisa; Karlsson, Antti; Tuominen, Samuli; Lassenius, Mariann I.; Aaltonen, Jaakko; Ranta, Martta; Kosunen, Mikko; Renlund, Mari; Lehtonen, Anne; Puolakka, Kari (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVES ': 'Patients with idiopathic inflammatory rheumatic diseases (IIRD) often have decreased working capacity resulting in indirect costs. However, data on patients’ short-term sick leave has been limited. This retrospective cohort study evaluated the number and length of sick leave, including short-term leave, and occupational healthcare resource utilization (HCRU) of the working-aged patients with IIRD compared to controls. ' ' METHODS ': 'The data on sick leave and occupational HCRU were gathered from the electronic medical records of the largest occupational healthcare provider in Finland from January 2012 to December 2019. Employed patients with an IIRD (including rheumatoid arthritis, spondyloarthritis, psoriatic and enteropathic arthritis, juvenile arthritis, and reactive arthritis) with at least a 12-months follow-up were identified and compared to age-, sex-, and follow-up matched controls without IIRD. ' ' RESULTS ': 'Altogether 5405 patients with IIRD were identified and compared with an equal number of controls. The patients incurred approximately 2.5 times more sick leave than controls: 21.7 versus 8.5 days per patient year, respectively. Short-term sick leave was common: 83% of sickness absence periods of the patients lasted 1–9 days and represented 30% of the total absenteeism. Loss of productivity due to lost workdays was on average €4572 (95% confidence interval €4352–4804) per patient year. Occupational HCRU was approximately 1.8 times higher among IIRD patients than controls. ' ' CONCLUSIONS ': 'Workers with an IIRD incur considerably more sick leave and use more occupational healthcare services than controls. Short sick leave not registered in national insurance registers constitute a significant portion of days off work among patients with IIRD.
Keywords: absenteeism; burden of disease; healthcare resource utilization; idiopathic inflammatory rheumatic disease; occupational healthcare; registry study; rheumatic disease; sick leave